Innovation, Research and Development Investment and Productivity in Colombian Firms - Maria Angelica Arbelaez; Monica Parra Torrado (Inter-American Development Bank (IDB), 2011)
This paper attempts to establish a formal relationship between innovation and productivity using Colombian firm-level data. It is found that the production of goods and services new to the firm and to the domestic market enhances firms` sales per worker, and innovation that results in introducing new goods and services to the international market boosts both sales and Total Factor Productivity (TFP). Innovation in processes likewise improves firms` productivity and sales. Finally, innovation in marketing and management increases sales per worker and enhances TFP when investment is made in Research and Development. The paper also studies the factors behind firms` decision to invest in innovation, the intensity of such investment and the returns to investment in innovation.
Keywords: C21; C31; C34; C35; L60; O31; O32; O14; O47; 330